Improving Fiscal Transparency to Raise Government Efficiency and Reduce Corruption Vulnerabilities in Central, Eastern, and Southeastern Europe - Akitoby, Bernardin (Departmental Papers; Departmental Paper ;, 2020)
This departmental paper investigates how countries in Central, Eastern, and Southeastern Europe (CESEE) can improve fiscal transparency, thereby raising government efficiency and reducing corruption vulnerabilities.